2020
DOI: 10.1177/1938640020980912
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating 3D Printing Into Your Practice: Lessons Learned

Abstract: Three-dimensional (3D) printing has greatly benefited medicine, manufacturing vital organs like skin, hearts, kidneys, and livers. Early studies on 3D printing in surgery have consistently reported decreased operative time and improved precision. This technology has gained popularity with orthopaedic surgeons in knee, hip, and shoulder surgeries because 3D printing is associated with enhancing osseointegration. However, this innovation is still not commonly used among foot and ankle surgeons; one reason is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Many studies have identified absolute differences in accuracy between programs for specific software, [15,18], described 3D printing workflows for different applications [19][20][21], and discussed printing best practices [22,23]. In this paper, the behaviors of different mathematical algorithms used in ROI segmentation and refinement are reviewed to highlight key features that can affect the transformation of medical images into 3D printable models.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified absolute differences in accuracy between programs for specific software, [15,18], described 3D printing workflows for different applications [19][20][21], and discussed printing best practices [22,23]. In this paper, the behaviors of different mathematical algorithms used in ROI segmentation and refinement are reviewed to highlight key features that can affect the transformation of medical images into 3D printable models.…”
Section: Introductionmentioning
confidence: 99%